Isolation, genotyping, and sub-genotyping of Newcastle disease virus from commercial broiler chickens in Northern Egypt - Ramzy, N; Elsamadony, H; Mekky, H; Fedawy, H; Saad, A (Journal of the Hellenic Veterinary Medical Society, 2024)
The governments seek to take care of livestock; it plays a significant role in the national economy because of the nutritional and economic importance of poultry protein. In poultry, viral diseases, including the Newcastle virus, are considered among the causes of profitable losses in poultry, which directly affect livestock and the general health of birds. Therefore, this research was conducted to follow up on the Newcastle disease virus recently circulating in commercial poultry farms in northern Egypt and compare the master amino acids that determine the velogeneity of the ND virus. In addition, this research will compare their relationship to the vaccines currently in use. A specific-pathogen-free chicken (EE-SPF) egg was used to isolate NDV from chicken farms. We then tested the inoculated allantoic fluids for NDV using the Hemagglutination Test and Hyper-Immune Serum against LaSota NDV. Furthermore, the F gene was molecularly characterized and sequenced. From 15 allantoic fluids that were positive for NDV, seven isolates (ON497007, ON497008, ON497010, ON497011, ON497012, and ON497013 and ON532692) out of 9 ND sequenced isolates clustered into sub-genotype VII.1.1 and the other 2 (ON497006 and ON497009) into sub-genotype XXI.1.1. All the isolates in this investigation carry the velogenic strain's characteristic velogenic motif 112RKQKR*F117. In conclusion, the circulating ND in vaccinated chicken flocks in Egypt genotype VII.1.1 and XXI.1.1. Moreover, there was a residual substitution between most isolates, and genotype VII vaccine strain (R/K), and autogenous vaccine strain (E/R) at position 78. These results are expected to help provide the latest characteristic information on NDV in northern Egypt.